Biotype Differentiation in the Genus Apluda Linn. I. Studies in the Apluda Population of Doon Valley - Thapa, Shashi; Agarwal, Anita; Srivastava, S. C.; Gupta, B. K. (Indian Forester, 1978)
An analysis of infraspecific variation in the population of Apluda mutica of Doon Valley has been presented. Nine biotypes have been isolated from the local population based on morphological characters. Botanical characterization of each of the nine biotypes isolated has been presented. Only such characters as are useful for actual differentiation of these biotypes are considered.